Identifying the Presence of Cyberbullying in Tamil-English Phonetic Words Using Browser Plugin - Md. Anwar R.; Victor P.A.; Rahim F.A.; Md Din M.; Abu Bakar A.; Latif A.A. (Springer Science and Business Media Deutschland GmbH, 2023)
Linguistics; Social networking (online); Cyber bullying; Detection; English phonetics; Language; Plug-ins; Research communities; Social media; Social media platforms; Social-networking; Web browser plug-in; Computer crime